The Mediating Function of Job Satisfaction in the Interaction Between Financial and Non-Financial Compensation and Employee Performance: Fungsi Mediasi Kepuasan Kerja dalam Interaksi antara Kompensasi Finansial dan Non-Finansial serta Kinerja Karyawan - Abrar, Unsul; Kurdi, Moh.; Anwar, Syaiful (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2026)
This study investigates how financial and non-financial compensation influence employee performance at PT Urchindize Madura, Indonesia, with job satisfaction as a mediating factor. Using a quantitative explanatory design, data were collected from all 46 employees and analyzed through partial least squares structural equation modeling (PLS-SEM). Results indicate that financial compensation significantly enhances job satisfaction, which in turn improves employee performance. Job satisfaction partially mediates the link between financial compensation and performance, while non-financial compensation shows no significant effect. These findings suggest that organizations should focus on competitive financial reward systems and re-evaluate non-financial benefits to better meet employee expectations. By strengthening compensation strategies grounded in employee satisfaction, companies can foster greater motivation, satisfaction, and productivity.